Design Formulation and Statistical Evaluation of Gastroretentive Microspheres of Rasagiline Mesylate for Parkinson’s Disease Using Design Expert - Prasanthi, R; Haarika, B; Selvamuthukumar, S (Indian Journal of Pharmaceutical Education and Research, 2023)
Introduction: Rasagiline mesylate is primarily prescribed to treat the symptoms of idiopathic Parkinson's disease works as irreversible inhibitor of mono amino oxidase. The microspheres were designed for extended retention of drug in gastrointestinal tract, resulting in superior absorption and enhanced bioavailability by oral route. Materials and Methods: The ionotropic gelation method was used to prepare the formulations RM1 to RM14 mucoadhesive microspheres with Sodium alginate, Calcium chloride, Carbopol 934, Xanthan gum, Chitosan of different concentrations were formulated in preliminary trials after performing preformulation studies such as FTIR, DSC. Optimization of Rasagiline mesylate mucoadhesive microspheres (RMS1 to RMS11) were done by optimizing independent variables such as polymer concentration i.e. Xanthan Gum (5 mg, 20 mg and 35 mg), a Stirring speed (500, 1000 and 1500 rpm) and dependent variables such as percentage entrapment efficiency, particle size and cumulative percent drug release. Optimization was done by using Design export 13 software by Central composite design from Response surface methodology. ANOVA explains the impact of independent variables on the dependent variables. For optimized formulation structural features determined by SEM and XRD. Results: In preliminary studies it was found that, apart from Chitosan, the formulations with Carbopol 934P had shown best mucoadhesion and drug release. The optimized formulation RMS12 (given by Design expert software) having 32.12 mg of Xanthan gum at 1500RPM showed 86.84% entrapment efficiency, 440µm particle size and 96.43 Cumulative percent drug release. Conclusion: It was concluded that the formulated Gastro retentive mucoadhesive microspheres of Rasagiline mesylate was found to be having best in vitro drug release.
Keywords: Rasagiline mesylate; Parkinson’s disease; Mucoadhesion; Microspheres; Design expert; Response surface methodology